2022
DOI: 10.4103/jips.jips_503_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of enamel wear against monolithic zirconia and layered zirconia after polishing and glazing: An in vitro study

Abstract: Aim: The aim of this study was to compare the wear behavior of human tooth enamel opposing monolithic zirconia and layered zirconia after glazing and polishing by a two-body wear mechanism using a wear simulator. Settings and Design: This In-vitro study was done in Department of Prosthodontics, Sri Sai College of Dental Research, Vikarabad. Materials and Methods: Zirconia specimens were divided into four groups ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…19 An in vitro study conducted by Shaik et al, compare the enamel wear against monolithic zirconia and layered zirconia after polishing and glazing, test results showed that Layered and Glazed group showed significantly greater enamel wear (1.01 mm ±0.11) compared to Monolithic Glazed group (0.76 mm ±0.17), followed by Layered Polished group (0.65 mm ±0.10) and Monolithic Polished group (0.19 mm ±0.08) showed the least enamel wear among the groups tested indicating that the mechanical polishing of zirconia is the best method to reduce the antagonist wear. 20 Providing the provisional prosthesis fabricated directly in the clinic significantly reduces the need for occlusal adjustment in the final definitive prosthesis as the prosthesis is duplicated from the adjusted provisional prosthesis. 21 In this case, the grinding and the adjustment of zirconia were avoided by adjustment of the provisional.…”
Section: Discussionmentioning
confidence: 99%
“…19 An in vitro study conducted by Shaik et al, compare the enamel wear against monolithic zirconia and layered zirconia after polishing and glazing, test results showed that Layered and Glazed group showed significantly greater enamel wear (1.01 mm ±0.11) compared to Monolithic Glazed group (0.76 mm ±0.17), followed by Layered Polished group (0.65 mm ±0.10) and Monolithic Polished group (0.19 mm ±0.08) showed the least enamel wear among the groups tested indicating that the mechanical polishing of zirconia is the best method to reduce the antagonist wear. 20 Providing the provisional prosthesis fabricated directly in the clinic significantly reduces the need for occlusal adjustment in the final definitive prosthesis as the prosthesis is duplicated from the adjusted provisional prosthesis. 21 In this case, the grinding and the adjustment of zirconia were avoided by adjustment of the provisional.…”
Section: Discussionmentioning
confidence: 99%
“…Ghazal showed that zirconia with different roughness significantly affects the amount of enamel wear [19]. Many scholars have shown that the surface polishing of zirconia produces less wear on natural teeth and less on its own [20][21][22][23][24][25][26][27]. The reason may be that there are a lot of cracks, pores, and other defects on the surface of all ceramic materials without polishing.…”
Section: Discussionmentioning
confidence: 99%
“…Minimal antagonist tooth wear is observed, and there is a high success rate for restorations in the posterior region [20] . Polished monolithic zirconia causes less wear to opposing natural teeth, and polished monolithic and layered zirconia surfaces showed less tooth wear compared to glazed monolithic and layered zirconia surfaces [21] . The antagonistic wear of zirconia enamel was similar to or greater than that of natural teeth but less than that of porcelain metal [22] .…”
Section: Antagonist Wearmentioning
confidence: 92%